Perioperative care for older people. (30th August 2022) - Partridge, Judith S L; Moonesinghe, S Ramani; Lees, Nicholas; Dhesi, Jugdeep K
Abstract: Increasing numbers of older people are undergoing surgery with benefits including symptom relief and extended longevity. Despite these benefits, older people are more likely than younger patients to experience postoperative complications, which are predominantly medical as opposed to surgical. Comprehensive Geriatric Assessment and optimisation offers a systematic approach to risk assessment and risk modification in the perioperative period. Clinical evidence shows that Comprehensive Geriatric Assessment and optimisation reduces postoperative medical complications and is cost effective in the perioperative setting. These benefits have been observed in patients undergoing elective and emergency surgery. Challenges in the implementation of perioperative Comprehensive Geriatric Assessment and optimisation services are acknowledged. These include the necessary involvement of a wide stakeholder group, limited available geriatric medicine workforce and ensuring fidelity to Comprehensive Geriatric Assessment methodology with adaptation to the local context. Addressing these challenges needs a cross-specialty, interdisciplinary approach underpinned by evidence-based medicine and implementation science with upskilling to facilitate innovative use of the extended workforce. Future delivery of quality patient-centred perioperative care requires proactive engagement with national audit, collaborative guidelines and establishment of networks to share best practice.